2016
DOI: 10.1681/asn.2016010112
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Peritoneal Dialysis

Abstract: Technical innovations in peritoneal dialysis (PD), now used widely for the long-term treatment of ESRD, have significantly reduced therapy-related complications, allowing patients to be maintained on PD for longer periods. Indeed, the survival rate for patients treated with PD is now equivalent to that with in-center hemodialysis. In parallel, changes in public policy have spurred an unprecedented expansion in the use of PD in many parts of the world. Meanwhile, our improved understanding of the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
362
1
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(387 citation statements)
references
References 205 publications
6
362
1
18
Order By: Relevance
“…Las complicaciones relacionadas con la técnica de diálisis peritoneal incluyen la esofagitis por reflujo, las hernias, la erosión del asa intestinal por presión del catéter, la peritonitis esclerosante y la pancreatitis. Las complicaciones relacionadas con la hemodiálisis incluyen náuseas, vómito, ansiedad, hambre, isquemia intestinal por hipotensión, sangrado digestivo por la heparina y pancreatitis inducida por hemólisis accidental 11,47,48 .…”
Section: Enfermedades Del Páncreas Y La Vía Biliarunclassified
“…Las complicaciones relacionadas con la técnica de diálisis peritoneal incluyen la esofagitis por reflujo, las hernias, la erosión del asa intestinal por presión del catéter, la peritonitis esclerosante y la pancreatitis. Las complicaciones relacionadas con la hemodiálisis incluyen náuseas, vómito, ansiedad, hambre, isquemia intestinal por hipotensión, sangrado digestivo por la heparina y pancreatitis inducida por hemólisis accidental 11,47,48 .…”
Section: Enfermedades Del Páncreas Y La Vía Biliarunclassified
“…A gyakorló klinikus szempontjából a jelenleg kezünkben lévő eszközök birtokában definiál-ható követendő irányelv, ha a legkisebb szükséges peritonealis dialízis mennyiséget biztosító, individualizált glü-kóztakarékos PD-rezsimet írjuk elő [40].…”
Section: Következtetésekunclassified
“…Likewise, allowing reimbursement of PD, but not HD, has permitted to increase the use of PD over HD in many Asian countries like Hong Kong, Vietnam, Taiwan, Thailand, as well as in New Zealand and Australia over recent years [42,43]. The major reasons of under utilization of PD modality include (1) lack or inadequate pre-dialysis education [44] and patient's awareness of RRT options [7,44,45], and in particular the suitability and advantages of PD modality, (2) insufficient or lack of focus on patients' training and encouragement and support, especially for anxious and unwell patients who might be nervous about participating in their own treatment [46][47][48], (3) lack or inadequate training of nursing staff and nephrologists in PD therapy [45,49], (4) insufficient encouragement and support of medical and nursing staff to guide patients to chose or implement PD modality as a possible first choice therapy [45,50], (5) lack or insufficient appreciation of the concept of "integrated renal replacement therapy (RRT) program" [1], and (6) inadequate preparation or lack of a proper set up of an independent PD unit [51,52].…”
Section: Open Access Http://scidocorg/ijcdtphpmentioning
confidence: 99%
“…More recent studies have shown that PD and in center HD provide similar short and long term survival [7]. PD has the benefits of preserving residual renal function [8], delaying the need for vascular access and helping patients with multiple vascular access failure, and constitutes a better option for older age groups especially those with cardiovascular disease [8,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation